Regional Differences in Anterior Cruciate Ligament Signal Intensity After Surgical Treatment. Issue 14 (December 2021) - Kiapour, Ata M.; Flannery, Sean W.; Murray, Martha M.; Miller, Patricia E.; Proffen, Benedikt L.; Sant, Nicholas; Portilla, Gabriela; Sanborn, Ryan; Freiberger, Christina; Henderson, Rachael; Barnett, Samuel; et al.
Background: Magnetic resonance–based measurements of signal intensity have been used to track healing of surgically treated anterior cruciate ligaments (ACLs). However, it is unknown how the signal intensity values in different regions of the ligament or graft change during healing. Hypotheses: (1) Normalized signal intensity of the healing graft or repaired ACL is heterogeneous; (2) temporal changes in normalized signal intensity values differ among the tibial, middle, and femoral regions; and (3) there are no differences in regional normalized signal intensity values 2 years postoperatively among grafts, repaired ACLs, and contralateral native ACLs. Study Design: Cohort study; Level of evidence, 2. Methods: Magnetic resonance imaging scans were analyzed from patients in a trial comparing ACL reconstruction (n = 35) with bridge-enhanced ACL repair (n = 65). The ACLs were segmented from images acquired at 6, 12, and 24 months postoperatively and were partitioned into 3 sections along the longitudinal axis (femoral, middle, and tibial). Linear mixed modeling was used to compare location-specific differences in normalized ligament signal intensity among time points (6, 12, and 24 months) and groups (ACL reconstruction, repair, and contralateral native ACL). Results: For grafts, the middle region had a higher mean normalized signal intensity when compared with the femoral region at all time points ( P < .01) but compared with the tibial region only at 6 months ( P < .01). For repaired ACLs, the middle region had a higher mean normalized signal intensity versus the femoral region at all time points ( P < .01) but versus the tibial region only at 6 and 12 months ( P < .04). From 6 to 24 months, the grafts showed the greatest reduction in normalized signal intensity in the femoral and middle regions (vs tibial regions; P < .01), while there were no regional differences in repaired ACLs. At 2 years after surgery, repaired ACLs had a lower normalized signal intensity in the tibial region as compared with reconstructed grafts and contralateral native ACLs ( P < .01). Conclusion: The results suggest that graft remodeling is location specific. Repaired ACLs were more homogeneous, with lower or comparable normalized signal intensity values at 2 years as compared with the contralateral native ACL and reconstructed grafts.